Relationship between Gastropod Abundance and Total Organic Material (BOT) Sediments in Mangrove Habitats in Gambesi Village, South Ternate District, Ternate City - Sembel, S. Nurul K.; Sabar, Mesrawaty; Benua, Rusmawati La; Subur, Riyadi; Fabanjo, Mohammad Abjan; Samman, Ardan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
In the mangrove ecosystem there are many gastropods which are one of the biological resources. As a habitat, Gastropods have high diversity and occupy the mangrove ecosystem. Organic detritus gets food supply through mangrove forests and makes an important contribution as the main source of food for biota living in the surrounding waters. The purpose of the study was to determine the diversity and abundance of gastropods, determine the concentration of total organic matter (BOT), analyze the relationship between the abundance of gastropods and total organic matter (BOT) in the sediment in the mangrove habitat and determine the condition of water quality at the research location of the coastal mangrove habitat of Gambesi Village. This study uses qualitative and quantitative methods. Sampling of gastropods was carried out using a block area measuring 20 x 20 m², which was carried out at low tide. The data analysis methods used were gastropod abundance, diversity index, organic matter content, simple linear regression. The results of the analysis of the highest gastropod abundance were at station 2 for the Terebralia sulcata species of 48 individuals and the lowest were at station 1 for the Nerita polita species of 3 individuals. The diversity index of station 1 is H’= 1.80 and station 2 is H’= 1.83, included in the medium diversity category. Station 1 sediment organic matter content is 34.20% in the high category and station 2 is 49.50% in the very high category. According to the simple regression test value, the correlation coefficient value ranges from around 0.8 <r ≤ 1.0 which proves that the abundance of gastropods has a large correlation with the organic matter content in the sediment.